Satisfaction evaluation of a just energy transition policy: evidence from China - Cheng, Haiyun; Dong, Mingniu; Zhou, Cheng (Frontiers in Environmental Science, 2023)
China has declared that it will achieve carbon neutrality by 2060, and energy transition will play a primary role in this process. This transition will encourage leapfrog development in efforts to achieve carbon neutrality. However, energy transition is often accompanied by social risks and injustices, which can be effectively addressed only by incorporating a just energy transition (JET) into the policy process. In this paper, 3 policy dimensions (material compensation, livelihood maintenance, and social development) associated with 13 policy designed to promote a JET in China are therefore categorized. In addition, the satisfaction of vulnerable groups with these policy approaches is evaluated according to the analytic hierarchy process (AHP) and via second-level fuzzy comprehensive assessment (FCA). The results of a satisfaction evaluation of 1,329 vulnerable people who have been laid off, forced to immigrate, fallen into energy poverty, had their rights and interests violated, etc., indicate that the overall satisfaction rate with a JET is 0.404 (the total values of “very satisfied” and “satisfied’), i.e., less than half. Accordingly, China still faces clear JET challenges and should rely on the collaborative promotion of four multiresponsible actors: the government, enterprises and trade unions, social organizations, and individuals. Only through this process can social resources be widely absorbed and mobilized to foster cross-boundary discussions and ensure that no vulnerable populations are left behind. This study thus enriches policy research on energy transition, providing a opportunity to expand the academic horizon of JET as a research field. Furthermore, this study may also inspire policymakers to pay more attention to JET, offering references for subsequent policy improvement.